A First Impression of Point-of-Care Testing in Spain: Spanish Society of Clinical Biochemistry Survey Results. Issue 4 (December 2017) - Lirón-Hernández, Francisco Javier; Oliver-Sáez, Paloma; Sánchez-Mora, Catalina; Rodríguez-Fraga, Olaia
Abstract : Abstract: The use of point-of-care testing (POCT) technology has increased every year worldwide. In Spain, there are no data about how these tests are used and where they are performed, and there is no clear vision of what is the role of laboratory regarding these tests. The POCT Committee, in the Spanish Society of Clinical Biochemistry, carried out a survey in order to find out what the situation is with POCT in the country from a laboratory POCT manager's point of view. The survey had 19 questions: 3 for segmentation, 1 for opinion, 13 to obtain specific information about POCT in their hospitals, and 2 about personal information. To enable a response, a survey link was shared in the Spanish Society of Clinical Biochemistry Web page. Responses were obtained via Google Docs Web page, where coworkers were requested to fill in the survey. The survey was answered by 140 laboratories, but only 126 of the responses were considered valid. The survey results generally showed that the situation in Spain is similar to that in other countries as documented by similar national surveys on POCT. The survey also demonstrated room for improvement in POCT practices and a need for governmental regulation to improve POCT processes.